Effects of some plants Extracts on Growth of some Candida Species Isolated from Oral Thrush, Thalassemia and Orthodontics Patients - Abbas Mohammed, Najwan; Muneam Fadhil, Noor (Al-Nahrain Journal of Science, 2025)
Due to the increase of microbial resistant to antibiotics in addition to recurrent fungal infections, the attentions in medicinal plants and herbs are increased. 52 samples of oral swabs were gathered from patients (male and female) with age average equal to 25.5 with different levels of clinical improvement (thrashing= 18, thalassemia = 15, orthodontics= 19). the samples were obtained from Diyala General Hospital and some health centers in Diyala province. Candida albicans was the most predominant spp. among different specimens’ groups fallowed by C. trupicalis, C. glabrata and lastly C. krusei. Candida spp are most prevalence in thalassemia patients fallowed by premature babies and orthodontics oral swabs, C. albicans were the most affected by Clutrimazole, C. trupicalis and krusei were resistant to Fluconazole C. krusei was the least affected by antifungals were used in this study. The culture results on media contain plant extracts showed a difference in the shape of the colonies growing on the media contained plant extracts, which indicates the effect of aqueous and alcoholic extracts of saffron, cloves, black seed and miswak on the growth of Candida species.